2019
DOI: 10.17516/1997-1397-2019-12-5-579-589
|View full text |Cite
|
Sign up to set email alerts
|

Modelling of Electrochemically Switchable Ion Transport in Nanoporous Membranes with Conductive Surface

Abstract: The impact of potential applied to the conductive surface of nanoporous membrane on the membrane potential at zero current is investigated theoretically on the basis of two–dimensional Space–charge model. The membrane separates two reservoirs with different salt concentrations. It is shown that the variation of applied potential from negative to positive values results in the continuous change of membrane selectivity from cation to anion. For equal ion diffusion coefficients, the dependence of membrane potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 33 publications
(50 reference statements)
0
2
0
Order By: Relevance
“…We consider the case when the injection at the cathode is proportional to the electric field strength z = 0 : q = a(t)E (E is electric field strength, and the modulation a(t) = a(1 + α sin(2πf t)) with amplitude α and frequency f is provided by oscillation of the potential on an ion-selective membrane [23] (or a grid electrode) near the cathode.…”
Section: Governing Equationsmentioning
confidence: 99%
“…We consider the case when the injection at the cathode is proportional to the electric field strength z = 0 : q = a(t)E (E is electric field strength, and the modulation a(t) = a(1 + α sin(2πf t)) with amplitude α and frequency f is provided by oscillation of the potential on an ion-selective membrane [23] (or a grid electrode) near the cathode.…”
Section: Governing Equationsmentioning
confidence: 99%
“…The SC model was revisited recently [19] by providing an essential simplification of working formulas, and further used to predict the ionic conductivity of carbon nanotubes [20]. The extension of SC model to the nanopores with constant surface potential was first suggested in [22] and applied to description of membrane potential at zero current in conductive nanopores [23][24][25]. It was demonstrated that the induced charge effects can essentially affect the magnitude of membrane potential.…”
Section: Introductionmentioning
confidence: 99%